Independent Qualitative Evaluative Study of Calmbirth Antenatal Classes - Crowther, S; Hollingshead, B; McAra-Couper, J; Donald, H; Hotchin, C (Springer Publishing Company, 2025)
High childbirth intervention rates impose risk to women and infants. It is imperative that ways to mitigate this are found. Calmbirth is an antenatal program that incorporates a variety of strategies that could be helpful. The aim of this qualitative evaluation was to explore the acceptability and experiences of attending Calmbirth antenatal classes. Eighteen individual and/or couple postnatal interviews were conducted. Analysis using a psycho-emotional conceptual framework was applied to data. The study found that Calmbirth courses empowered participants, increased their health literacy, and provided them with more personal psychosocial coping strategies. While some participants found the classes not helpful, others experienced a positive reframing of childbirth. Although Calmbirth is acceptable and experienced positively by most women and partners, further work is required to address broader sociocultural influences in places of birth.
Keywords: Calmbirth; antenatal; childbirth; education; mindfulness; 4204 Midwifery; 42 Health Sciences; Behavioral and Social Science; Prevention; Clinical Research; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; Reproductive health and childbirth; 3 Good Health and Well Being; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 4204 Midwifery